MENTAL HEALTH, PAIN, AND RISK OF DRUG MISUSE: A NATIONWIDE COHORT STUDY - Glei, Dana A. (Addict Behav, 2020)
Evidence suggests that rising drug misuse, particularly of prescription painkillers, is more closely linked with period increases in reported pain among Americans of the same age range than with deterioration in mental health, but it is unclear whether those cross-sectional associations reflect causal effects of pain and mental health on drug misuse. Using data from the 1995-96, 2004-05, and 2013-14 waves of a nationwide cohort study, we evaluate the effects of pain and mental health on subsequent misuse of prescription painkillers and sedatives. Logistic regression is applied to model drug misuse (separately for painkillers and sedatives) as a function of predictors measured at the previous wave; respondents who reported misuse of that drug type at the prior wave are excluded from the analysis. Mental health is an important predictor of both painkiller and sedative misuse, whereas pain plays a much bigger role in painkiller misuse. Frequency of joint aches and stiffness has the strongest effect on subsequent painkiller misuse, although mental health yields substantial incremental predictive ability above and beyond pain. Negative affect, positive affect, and psychological well-being have notable effects on sedative misuse, while pain (particularly backache) makes only a small incremental contribution to sedative misuse. We suspect that increases over time in pain levels may have played a bigger role than mental health in explaining the rise in prescription painkiller misuse and may have contributed to growing misuse of sedatives. In contrast, deteriorating mental health was probably more important in explaining the rise of sedative misuse.